Is there a home field advantage in global markets? - Jagannathan, Murali; Jiao, Wei; Karolyi, G. Andrew (Journal of Financial Economics, 2022)
International equity mutual funds increasingly hire managers from countries linked to their geographic mandate. We show these funds with “home-linked managers” exhibit a strong bias to invest in stocks of the managers' home countries and attract more flows. Portfolios of stocks from countries in which a fund has a home-field advantage outperform those managed by funds without home-linked managers. We are unable to identify specific sources of an information advantage associated with the home-linked manager's performance. But an analysis of fund flows reveals a role of investor trust in home-linked managers earned primarily through past superior performance.